Romaria da Medianeira e estudos culturais: a construção dos modos de ver dos futuros docentes de artes visuais - Souza, Carla Farias (2008)
The present research has been developed in the Line of Education and Arts/PPGE and had the purpose of constructing a possibility of educative practice for the teaching of Visual Arts with the thematic of reading of images relative to the Pilgrimage of Medianeira that were analyzed from Franz theoretical focus (2003) and the Cultural Studies by applying Costa (2003), Giroux (1995), Hall (1997), Silva (1995) and Veiga-Neto (2000). We have analyzed the narratives existent in the reading of the images of the Celebration of Nossa Senhora Medianeira and in the visual workmanships that compose the market aspects of the procession, besides problematizing the aspects of the local religious culture in the basic formation of professors. The research has a qualitative approach through a case study accomplished with academics of the course of Degree in Visual Arts of the Federal University of Santa Maria. The instruments applied as means of data collection were the participant observation, the documental analysis, the interview, the field diary and the portfolio. As a result of the investigation, points of view amongst the subjects were noticed, in the cultural background analysis of the image, which differentiate in depth and criticism when one starts from a point of view crystallized by the religious discourse and the other allows a more critical connotation, going beyond a mere superficial reading. Thus, we see the importance of the construction of the glance in the Visual Arts professors formation on a cultural product - as a procession - inserted within the approach of the cultural studies, since it problematize the context of the power relations present in the image, possibly exerting influence on its critical understanding.